Acute Loss of Apolipoprotein E Triggers an Autoimmune Response That Accelerates Atherosclerosis. Issue 8 (August 2018) - Centa, Monica; Prokopec, Kajsa E.; Garimella, Manasa G.; Habir, Katrin; Hofste, Lisa; Stark, Julian M.; Dahdah, Albert; Tibbitt, Chris A.; Polyzos, Konstantinos A.; Gisterå, Anton; Johansson, Daniel K.; Maeda, Nobuyo N.; et al.
Abstract : Objective—: Dyslipidemia is a component of the metabolic syndrome, an established risk factor for atherosclerotic cardiovascular disease, and is also observed in various autoimmune and chronic inflammatory conditions. However, there are limited opportunities to study the impact of acquired dyslipidemia on cardiovascular and immune pathology. Approach and Results—: We designed a model system that allows for the conversion to a state of acute hyperlipidemia in adult life, so that the consequences of such a transition could be observed, through conditionally deleting APOE (apolipoprotein E) in the adult mouse. The transition to hypercholesterolemia was accompanied by adaptive immune responses, including the expansion of T lymphocyte helper cell 1, T follicular helper cell, and T regulatory subsets and the formation of germinal centers. Unlike steady-state Apoe −/− mice, abrupt loss of APOE induced rapid production of antibodies recognizing rheumatoid disease autoantigens. Genetic ablation of the germinal center reduced both autoimmunity and atherosclerosis, indicating that the immune response that follows loss of APOE is independent of atherosclerosis but nevertheless promotes plaque development. Conclusions—: Our findings suggest that immune activation in response to hyperlipidemia could contribute to a wide range of inflammatory autoimmune diseases, including atherosclerosis. Abstract : Supplemental Digital Content is available in the text.